2016
DOI: 10.1038/srep33084
|View full text |Cite
|
Sign up to set email alerts
|

Holographic intravital microscopy for 2-D and 3-D imaging intact circulating blood cells in microcapillaries of live mice

Abstract: Intravital microscopy is an essential tool that reveals behaviours of live cells under conditions close to natural physiological states. So far, although various approaches for imaging cells in vivo have been proposed, most require the use of labelling and also provide only qualitative imaging information. Holographic imaging approach based on measuring the refractive index distributions of cells, however, circumvent these problems and offer quantitative and label-free imaging capability. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…2(a) (Visualization 6). Individual erythrocytes with a parachute-like shape [32][33][34] could be clearly identified in the single frame obtained with the speed of 30 frames per second. While the intravenously injected 40 kDa of FITC-dextran fully filled up the lumen of capillary including the glycocalyx layer on the endothelial cell [35,36], it was noticeable that the flowing erythrocytes did not directly contact the endothelial cell surface as shown in Fig.…”
Section: Real-time Visualization Of Flowing Erythrocyte and Analysis mentioning
confidence: 97%
“…2(a) (Visualization 6). Individual erythrocytes with a parachute-like shape [32][33][34] could be clearly identified in the single frame obtained with the speed of 30 frames per second. While the intravenously injected 40 kDa of FITC-dextran fully filled up the lumen of capillary including the glycocalyx layer on the endothelial cell [35,36], it was noticeable that the flowing erythrocytes did not directly contact the endothelial cell surface as shown in Fig.…”
Section: Real-time Visualization Of Flowing Erythrocyte and Analysis mentioning
confidence: 97%
“…We exploit the fact that RI is an intrinsic optical property of materials and linearly proportional to material concentration (26). Recently, measuring 3D RI distributions has been widely applied to study the pathophysiology of various biological samples, such as red blood cells (28)(29)(30)(31)(32), white blood cells (33)(34)(35), cancer cells (36)(37)(38)(39)(40)(41)(42), phytoplankton (43), and bacteria (44)(45)(46). Thus, dry mass of non-aqueous molecules making up the cell can be measured from RI information without any invasive labeling process.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the TPM technique, Park et al [100] found out that the volume and surface area of the cord RBCs of newborn infants are much larger than those of the RBCs of non-pregnant women, and these cord RBCs are also flatter than those of adults. By monitoring stored blood without the preservation solution CPDA-1 for around 6 weeks, the 3D RI tomograms showed that RBCs experience significant morphological changes during this storage period, transforming from disco-cytes to echinocytes on day 5 and finally becoming spherocytes after 2 weeks [101]. Quantitatively, the RBC volume, surface area, and sphericity parameters were compared between stored blood with and without CPDA-1 after different storage periods [101].…”
Section: Applicationsmentioning
confidence: 99%
“…By monitoring stored blood without the preservation solution CPDA-1 for around 6 weeks, the 3D RI tomograms showed that RBCs experience significant morphological changes during this storage period, transforming from disco-cytes to echinocytes on day 5 and finally becoming spherocytes after 2 weeks [101]. Quantitatively, the RBC volume, surface area, and sphericity parameters were compared between stored blood with and without CPDA-1 after different storage periods [101]. Besides RBCs, TPM has also been widely utilized to study the morphological features of other types of eukaryotic cells, such as white blood cells [Fig.…”
Section: Applicationsmentioning
confidence: 99%